2018
DOI: 10.3390/nu10111807
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Aqueous Extract of Withania somnifera on Strength Training Adaptations and Recovery: The STAR Trial

Abstract: Withania somnifera (Ashwagandha) is an Ayurvedic herb categorized as having “rasayana” (rejuvenator), longevity, and revitalizing properties. Sensoril® is a standardized aqueous extract of the roots and leaves of Withania somnifera. Purpose: To examine the impact of Sensoril® supplementation on strength training adaptations. Methods: Recreationally active men (26.5 ± 6.4 years, 181 ± 6.8 cm, 86.9 ± 12.5 kg, 24.5 ± 6.6% fat) were randomized in a double-blind fashion to placebo (PLA, n = 19) or 500 mg/d Sensoril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 21 publications
0
36
0
Order By: Relevance
“…Moreover, roots are consumed as a dietary supplement. Previous pharmacological studies on W. somnifera have revealed that extracts of W. somnifera exhibit a protective role against bromobenzene-induced oxidative damage in the rat liver [7], as well as increase the exercise performance [8]. Similarly, a recent study on W. somnifera extracts reported its therapeutic role in stroke repair through its anti-apoptotic and anti-oxidant properties [9].…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, roots are consumed as a dietary supplement. Previous pharmacological studies on W. somnifera have revealed that extracts of W. somnifera exhibit a protective role against bromobenzene-induced oxidative damage in the rat liver [7], as well as increase the exercise performance [8]. Similarly, a recent study on W. somnifera extracts reported its therapeutic role in stroke repair through its anti-apoptotic and anti-oxidant properties [9].…”
Section: Introductionmentioning
confidence: 96%
“…[ 117 ], Rhodiola rosea [ 118 ], Cordyceps militaris [ 119 ], and Rhodiola rosea + Cordyceps sinensis [ 120 ]. A root extract that warrants special attention is Withania somnifera (most known as ashwagandha) given some research have found ergogenic effects in athletic [ 121 , 122 ] and physically active individuals [ 123 ]. Moreover, the adaptogenic, anti-inflammatory, and antioxidant properties of ashwagandha [ 124 , 125 , 126 ] turns this herbal extract into a potential strategy to optimize recovery and promote exercise-induced adaptations.…”
Section: Resultsmentioning
confidence: 99%
“…Several clinical trials involving the administration of WS aqueous extract found an increase in the overall muscle strength ( Wankhede et al, 2015 ) ( Ziegenfuss et al, 2018 ). Rhabdomyolysis is associated with altered levels of serum urea and creatinine ( Walid, 2008 ).…”
Section: Probable Role Of Withania Somnifera In Covid-19 Pathophysiologymentioning
confidence: 99%